VD_FINDINFO Décision / 2013 / 121 vom 4. Mai 2006 - VD Tribunal cantonal (2006)
INTERNEMENTDROIT PÉNAL, MESURE THÉRAPEUTIQUE INSTITUTIONNELLE | 59 CP, 64a CP, 64b CP, 65 CP, 363 CPP (CH), 393 al. 1 let. b CPP (CH)